PEDAGOGICAL CONTENT KNOWLEDGE DEPELOPMENT OF SCIENCE PROSPECTIVE TEACHERS IN PROFESSIONAL PRACTICE PROGRAM - Rochintaniawati, Diana; Widodo, Ari; Riandi, Riandi; Herlina, Lina (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The study of â€œPedagogical Content Knowledge Development of Science Prospective Teachers in Professional Practice Programâ€ was conducted in one junior high school located in Bandung. The purpose of the study was to analyze the level and pattern of science prospective teachersâ€™ PCK development as measured by CoRe. The study involved students who enrolled professionals practice program. Mixed methods, quantitative and qualitative research was utilized as a method in the study. Data collected by the coding and scoring of the CoRe instruments were analyzed quantitatively; and data gained from observation, documentation, and interviews were analyzed qualitatively. The results showed that the PCK of prospective teachers are in the maturing PCK (level 3) and growing PCK (level 2). There are two patterns of PCK development showed by prospective teachers i.e. rising and fluctuative. The prospective teachers who are in the mature PCK show the pattern of rising, whereas prospective teachers who are in the growing PCK show fluctuative pattern. The study reveals that external and internal factors influenced the development of PCK. The pattern of guidance, lesson study activities, and intensity guidance are external factors that influenced the pattern of prospective studentsâ€™ PCK development. Psychological effect that exists between teachers and students, the motivation of self to expand the horizons of knowledge, communication skills, and teaching experiences are the internal factors that influenced the development of prospective teacher PCK. The study suggests that the development of prospective teachers PCK in the program can be improved when supervisor and prospective teachers put consideration to those internal and external factors that influence the development of PCK.